A new functional assay for the diagnosis of X-linked inhibitor of apoptosis (XIAP) deficiency. (24th April 2014) - Ammann, S; Elling, R; Gyrd-Hansen, M; Dückers, G; Bredius, R; Burns, S O; Edgar, J D M; Worth, A; Brandau, H; Warnatz, K; zur Stadt, U; Hasselblatt, P; et al.
Summary: X-linked inhibitor of apoptosis (XIAP) deficiency, caused by mutations in BIRC4, is an immunodeficiency associated with immune dysregulation and a highly variable clinical presentation. Current diagnostic screening tests such as flow cytometry for XIAP expression or lymphocyte apoptosis assays have significant limitations. Based on recent evidence that XIAP is essential for nucleotide-binding and oligomerization domains (NOD)1/2 signalling, we evaluated the use of a simple flow cytometric assay assessing tumour necrosis factor (TNF) production of monocytes in response to NOD2 stimulation by muramyl dipeptides (L18-MDP) for the functional diagnosis of XIAP deficiency. We investigated 12 patients with XIAP deficiency, six female carriers and relevant disease controls. Irrespective of the diverse clinical phenotype, the extent of residual protein expression or the nature of the mutation, the TNF response was severely reduced in all patients. On average, L18-MDP induced TNF production in 25% of monocytes from healthy donors or female carriers, while fewer than 6% of monocytes responded in affected patients. Notably, the assay clearly discriminated affected patients from disease controls with other immunodeficiencies accompanied by lymphoproliferation, hypogammaglobulinaemia or inflammatory bowel disease. Functional testing of the NOD2 signalling pathway is an easy, fast and reliable assay in the diagnostic evaluation of patients with suspected XIAP deficiency.